2020
DOI: 10.3390/rs12091429
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Natural Forest Remnants with Multi-Source and Multi-Temporal Remote Sensing Data for More Informed Management of Global Biodiversity Hotspots

Abstract: Global terrestrial biodiversity hotspots (GBH) represent areas featuring exceptional concentrations of endemism and habitat loss in the world. Unfortunately, geospatial data of natural habitats of the GBHs are often outdated, imprecise, and coarse, and need updating for improved management and protection actions. Recent developments in satellite image availability, combined with enhanced machine learning algorithms and computing capacity, enable cost-efficient updating of geospatial information of these alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 91 publications
(164 reference statements)
2
8
0
2
Order By: Relevance
“…It is shown that the average area of PAs, which ensures the maintenance of 75% of the typological diversity of communities in the study region, is about 1000 ha. A similar conclusion was obtained in the work [68].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is shown that the average area of PAs, which ensures the maintenance of 75% of the typological diversity of communities in the study region, is about 1000 ha. A similar conclusion was obtained in the work [68].…”
Section: Discussionsupporting
confidence: 91%
“…Recognition of typological units was carried out at the maximum level of hierarchy detail (overall accuracy 0.59). Similar model accuracy (0.57) was obtained in the closed canopy evergreen natural forest study in Tanzania and Kenya [68]. The relatively low accuracy of our model is explained by the complex polydominant composition of the tree layer, the combination of nemoral and boreal species groups in subordinate layers, and the silvicultural origin of most coniferous communities.…”
Section: Discussionsupporting
confidence: 73%
“…This urban growth will affect terrestrial ecosystems and will produce an increase in demands on the services they provide [3]. The United Nations (UN) exposes the importance that environmental services and ecosystems offer to human beings as natural goods and services, and on which social well-being and economic development depend directly, and which are currently declining globally at a dizzying rate [4,5]. On the other hand, the establishment of forest ecosystems requires a minimum of conditions that allow the growth of trees.…”
Section: Introductionmentioning
confidence: 99%
“…An ecological reserve or nature reserve is a semi-protected area, of importance for wildlife, flora, or fauna, or with geological features of special interest that is protected and managed by man, for the purpose of conservation, and to provide opportunities for research and education. It is a human delimitation where activities harmful to the environment are prohibited, which is established mainly to conserve biological diversity of regional and local interest, and maintain the continuity of essential ecological processes, in addition to the provision of environmental services derived from them [5,82,122 Cross Border Biophysical Forest Phenomena: the phenomenon of shyness of the tree canopy consists of a limited growth of the treetops, so that the leaves and branches of adjacent trees do not touch each other, producing figures and patterns with the background sky when observing the trees from the ground. The shyness of the crown has been observed in certain species of European oak and pine, and species of tropical and subtropical habitats.…”
mentioning
confidence: 99%
See 1 more Smart Citation